Extraction, Characterization, and In Vitro Biological Activity of Polyphenols from Discarded Young Fig Fruits Based on Deep Eutectic Solvents - Qinqiu Zhang; Yue Peng; Yi Xu; Fan Li; Shuxiang Liu; Danka Bukvicki; Qing Zhang; Shang Lin; Miaomiao Wang; Tianyi Zhang; Dingtao Wu; Wen Qin (Antioxidants, 2024)
(1) Background: Discarded young fig fruits (DYFFs) result in a waste of resources, such as sparse fruits and residual fruits, and there has been no research on the relationship between phenolic compounds and biological activity in DYFFs (2) Methods: Different deep eutectic solvents (DESs) and 80% ethanol were used to prepare DYFF extracts, and polyphenol extraction efficiency and bioactivities in the DYFFs extracts were compared. (3) Results: More than 1700 phytochemicals were identified in DYFFs, and thirteen of these typical phenolic compounds were analyzed quantitatively; chlorogenic acid, rutin, luteolin 8-C-glucoside, and epicatechin are the main polyphenols in DYFFs, especially chlorogenic acid with 2720–7980 mg/kg. Ferulic acid, caffeic acid, epicatechin, (+)-catechin, luteolin 8-C-glucoside, rutin, hesperetin, and chlorogenic acid showed different degrees of correlation with in vitro antioxidant activity. Moreover, the highest total phenol content found in the extracts of ChCl-Ethylene glycol (Choline chloride:Ethylene glycol = 1:2) was 8.88 mg GAE/g DW, and all quantitatively analyzed phenolic compounds had high levels in various DESs and 80% ethanol. The 80% ethanol and Choline chloride (ChCl) solvent system showed the greatest antioxidant properties, and the Choline chloride-Urea (Choline chloride: Urea = 1:2) extract of DYFFs exhibited the highest inhibitory activity. (4) Conclusions: DESs have demonstrated potential as promising green solvents, especially the ChCl solvent system, which facilitates the extraction of polyphenols.